ANALYSIS OF DETERMINANTS OF POOR POPULATION IN CENTRAL JAVA 2008-2017 - Wibowo, Ana Rahmawati; Khoirudin, Rifki (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2019)
One of the indicators socio-economic the success of development is a decrease in the number of poor people. Central Java is the province with the second largest number of poor people after East Java Province. This study aims to determine the effect of population growth rate, GDP per capita life expectancy (AHH), mean years of schooling (RLS) and purchasing power parity simultaneously and partially on the number of poor people in Central Java from 2008-2017. This study uses secondary data by using program Stata 14, the analysis technique used is multiple linear regression panel data. The results of the study showed that the population growth rate, GDP per capita, life expectancy (AHH), mean years of schooling (RLS) and purchasing power parity simultaneously have a significant effect on the number of poor people. Partially, population growth rate, life expectancy, and means years of schooling have a negative and significant influence on the number of poor people. While the GDP per capita and purchasing power parity do not have a significant effect on the number of poor people in Central Java. Various government policies and programs should continue to be rolled out to isolated areas so that increased income can be balanced with equitable development.